Screening local feed ingredients of Benin, West Africa, for fish feed formulation - KAYODE, A. PIERRE POLYCARPE; CHABI, Ifagbémi Bienvenue (My University, 2020)
The cost of fish feed is a major constraint to fish farming in Sub-Sahara Africa. In the aquaculture value chain, feed is a determining factor and accounts for 60-75% of the total cost of fish production in many African countries. Therefore, 284 actors from all eight agro-ecological areas of Benin were interviewed and 28 local feed ingredients were collected as alternative ingredients for new fish feed formulations for, predominantly, Clarias gariepinus and Tilapia niloticus. Three categories of feeds were used, namely imported (84% of farmers), locally produced to complement imported feeds (76%) and natural ingredients (81%). The main imported feeds were from the Netherlands (59% of farmers), Ghana (52%) and France (15%). Natural ingredients were mostly Moringa leaves (52%), cassava leaves (26%) and maggots (43%). The best available ingredients were cereal bran, soybean meal, cottonseed meal, cassava chips, palm kernel cake, soybean and maize. Regarding proteins, the most promising ingredients were trash fish (680 g/kg), poultry viscera (590 g/kg), soybean meal (450 g/kg) and cottonseed meal (410 g/kg). Oyster shell had the highest ash content (960 g/kg), followed by whole garden snail meal (700 g/kg). The highest carbohydrate contents were for tapioca (890 g/kg), lafun (880 g/kg) and cassava chips (810 g/kg). Overall, this study revealed a diversity of local feed ingredients available in Benin to formulate fish feeds with adequate nutritional composition to enable efficient fish farming
Keywords: Fish feed; Ingredient; Nutritional quality; Availability Cost; Clarias gariepinus